(untitled) (Research, Society and Development, 2022)
The objective was to analyze, according to the literature, the importance of paternal support in breastfeeding. This is an integrative review, carried out from March to June 2020. The descriptors paternity, breastfeeding, nursing and women’s health were used, based on: SciELO, LILACS, BDENF. There were 7 articles, of which, it was observed that the presence of the father in exclusive breastfeeding, in addition to strengthening the family bond, highlights its importance in the process, health professionals are of paramount importance in this process, for maintaining adherence, care, guidance and expanding the support network. It was evidenced that the father has a great influence on breastfeeding, because without this help the breastfeeding process and the mother’s adherence become difficult, given all the difficulties. It is suggested that health teams plan strategies that can guide and encourage the effective participation of the father in providing support to women in breastfeeding.